Aesthetics for everyday quality: one way to enrich healthcare improvement debates. Issue 4 (24th February 2022) - Cribb, Alan; Pullin, Graham
Abstract : In this paper we seek to illuminate the importance of aesthetics for healthcare quality and encourage more explicit discussion of aesthetics in healthcare improvement scholarship and practice. We hope to contribute to and help develop the hinterland between arts-based initiatives in healthcare and the 'normal business' of healthcare quality improvement. Our broad contention is: (1) That aesthetic considerations should be seen as of universal relevance across quality debates (2) That they never be assumed to have a marginal or even secondary status; and (3) That taking aesthetic considerations seriously calls for explicit discussion of associated uncertainties and dilemmas and a readiness to welcome aesthetics expertise into improvement debates.